Bilateral XEN Gel Stent Implantation in Juvenile-Onset Open-Angle Glaucoma - Klug, Emma (Case Rep Ophthalmol, 2020)
The purpose of the current case is to report the successful management of juvenile-onset open-angle glaucoma with bilateral XEN Gel Stent (Allegran Inc., Irvine, CA) implantation in a patient first diagnosed during pregnancy with co-existing dysautonomia. Treatment with the XEN Gel Stent provided dramatic reductions in intraocular pressure (IOP), and glaucoma medications sustained up to 23 months postoperatively. The success of this case may suggest that this minimally invasive procedure could be an effective treatment option for younger patients who require substantial reductions in IOP and glaucoma medication burden.